Exploration of Secondary Metabolites in Black Pomegranate Peel Extract (Punica granatum L.) as Antioxidants Using DPPH Method - Rofiidah, Anisatul; Innaya, Allinha Yusfin; Putri, Nela Vede Rhofa; Maulida, Hilda Jihan; Dewi, Lina Purnama; Al Shofura, Nadya Raisa; Badria, Shoimatul Umi; Faiza, Hilda Wahyu; Hidayah, Ulfa; Ramadhani, Mieta Widya; Rafsanjani, Ramizard; Januarista, Terra; Faisal, Faisal; Ramadhan, Majida (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
Pomegranate (Punica granatum) is a plant that contains secondary metabolite compounds that can be used as medicinal content. Black pomegranate contains the highest secondary metabolites compared to red pomegranate and white pomegranate, the skin of the pomegranate contains flavonoids, phenols, tannins, and saponins. This study aims to determine the antioxidant activity of black pomegranate peel extract (Punica granatum L.) with the DPPH method. DPPH method is a method to determine the antioxidant activity in the sample by looking at its ability to counteract the free radical compound 2,2-diphenyl-1-picrylhydrazyl. The results of testing the antioxidant activity of black pomegranate skin (Punica granatum L.) produced an IC50 value of 47.51 ppm which can be concluded that black pomegranate skin is classified as very strong. This research is important because there has not been much research on black pomegranate, especially its skin, so there is a need for additional expansion and renewal of the species. In addition, it can be used as the main basis for the advancement of natural materials, especially in the field of health.